Studying PAR-Dependent Chromatin Remodeling to Tackle PARPi Resistance. Issue 7 (July 2021) - Andronikou, Christina; Rottenberg, Sven
Abstract : Histone eviction and chromatin relaxation are important processes for efficient DNA repair. Poly(ADP) ribose (PAR) polymerase 1 (PARP1) is a key mediator of this process, and disruption of PARP1 activity has a direct impact on chromatin structure. PARP inhibitors (PARPis) have been established as a treatment for BRCA1- or BRCA2-deficient tumors. Unfortunately, PARPi resistance occurs in many patients and the underlying mechanisms are not fully understood. In particular, it remains unclear how chromatin remodelers and histone chaperones compensate for the loss of the PARylation signal. In this Opinion article, we summarize currently known mechanisms of PARPi resistance. We discuss how the study of PARP1-mediated chromatin remodeling may help in further understanding PARPi resistance and finding new therapeutic approaches to overcome it. Highlights: Despite the success of PARP inhibitors (PARPis) in targeting BRCA-deficient tumors, the emerging PARPi resistance remains a major clinical hurdle. Various PARPi resistance mechanisms have been unraveled to date, but their clinical relevance remains to be determined and they do not seem to explain all cases. PARP1 mediates variable cellular processes through chromatin remodeling, which is crucial for replication, transcription, and the response to DNA-targeting chemotherapy. It is important to study in more detail how PARP inhibition and subsequent PARPi resistance affect histone eviction and chromatin remodeling. Targeting of PAR-regulated chromatin modifiers like ALC1, APLF, or the FACT complex may open a new route to understand and tackle PARPi resistance.